IBM USAHA GENTENG PEJATEN, SENTRA PEMBUATAN GENTENG DI TABANAN - Sunarsih, Ni Made; Mendra, Ni Putu Yuria; Wirasutama, Cokorda Putra (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2017)
Pejaten region is famous as a producer of tile, where the people of this area most of the business is from the manufacture of tile, therefore this business should get attention because it is a very supportive business in the construction of houses and buildings, especially for property business. Although many people who own tile business, but there are still tile business in this area that is still minimal equipment and marketing methods, so it needs to be considered.Partners in this program is Tri Darma Putra's tile business owned by Mrs. Ni Made Sikiati. Partner issues are in production and management aspects covering 1) Dryer rack has been eaten by termites, 2) production process has not paid attention to health because workers do not use masks, 3) The rest of the defective or damaged production are left scattered, 4) not yet have bookkeeping and administration system inadequate, 5) marketing systems, and 6) have no nameplate and business cards. The outcomes that will be produced in this program include 1) Improving the dryer rack, 2) providing masks, 3) training and bookkeeping assistance, 4) online marketing assistance, and 5) nameplate and business cards for partners, and 6) procurement drums for defective or damaged production waste.